2008
DOI: 10.1111/j.1752-1688.2008.00206.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Snow Cover Conditions on the Hydrologic Regime: Case Study in a Pluvial‐Nival Watershed, Japan1

Abstract: Hydrologic monitoring in a small forested and mountainous headwater basin in Niigata Prefecture has been undertaken since 2000. An important characteristic of the basin is that the hydrologic regime contains pluvial elements year-round, including rain-on-snow, in addition to spring snowmelt. We evaluated the effect of different snow cover conditions on the hydrologic regime by analyzing observed data in conjunction with model simulations of the snowpack. A degree-day snow model is presented and applied to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…The dependence of the DOY with minimum 7-day discharge on the DOY of maximum SWE was confirmed in our study. Similar dependences were found also in Whitaker et al (2008), using the timing of the first significant snowmelt event instead of the DOY of maximum SWE. A negative trend in the number of days with discharge below a specified threshold in the case of increasing maximum SWE was proved.…”
Section: The Role Of Catchment Propertiessupporting
confidence: 62%
“…The dependence of the DOY with minimum 7-day discharge on the DOY of maximum SWE was confirmed in our study. Similar dependences were found also in Whitaker et al (2008), using the timing of the first significant snowmelt event instead of the DOY of maximum SWE. A negative trend in the number of days with discharge below a specified threshold in the case of increasing maximum SWE was proved.…”
Section: The Role Of Catchment Propertiessupporting
confidence: 62%
“…was found to be relatively more sensitive to future temperature and precipitation scenarios than lower-elevation bands. Further, Zappa and Kan (2007) demonstrated that the presence of above-average snow resources contributed to mitigating the effects of the 2003 summer drought in some highelevation areas within the Swiss Alps.…”
mentioning
confidence: 99%
“…Takiya River in northern Niigata Prefecture is a tributary of the Miomote River in the heavy snowfall Japan Sea Region (Figure 1). Long-term hydrological monitoring has been undertaken here since 2000, giving a valuable database on snow processes and the natural hydrological regime in a relatively undisturbed basin (Whitaker et al, 2008). Basin area is 19.45 km 2 with an elevation range of 40-950 m. The stream channel remains unfrozen even during the winter period, allowing stream gauging all year-round.…”
Section: Study Sitementioning
confidence: 99%
“…The value of the precipitation factor for Zone 1 (Table II) is largely accounting for the under-catch of snowfall by the Miomote AMeDAS gauge, which does not have a wind-shield. In addition, Whitaker et al (2008) analyzed the monthly water balance of the basin by using estimated evapotranspiration to derive values for the Table I. Calculation of precipitation for each elevation zone (mean zonal elevation given in parenthesis)…”
Section: Climate Datamentioning
confidence: 99%
See 1 more Smart Citation